Mathematics placement test scores & its significance: A Case study. - Sathissan Ragavan, * (2013)
The aim of this study is to examine the relationship between Mathematics placement test scores and students’ final scores in the Mathematics course. Questions have been raised regarding the importance of Mathematics placement tests in placing students in the most suitable Mathematics course. The study examines the importance of the Mathematics placement test and its significant contribution to students’ performance in Mathematics course taken at pre-university level. Mathematics placement tests undeniably fulfill its purpose of providing preliminary Mathematics course placement recommendation, encouraging students to register themselves for the most appropriate Mathematics course based on their competence, thus helping students to perform better. The study will focus on the sample of 58 students enrolled in the Monash University Foundation Year (MUFY) at Sunway College Johor Bahru in January 2013. The correlation between their Mathematics Placement Test scores and their final marks in the Mathematics Unit 1(equivalent to Year 12 Mathematics) and Fundamental Mathematics Unit 1 (equivalent to Year 11 Mathematics) is analysed.